Altering the O/C ratio of lignin derived monomers without sacrificing atom efficiency - Singh, Dheerendra; Dhepe, Paresh L. (ChemistrySelect, 2019)
Synthesis of platform and fuel grade chemicals from lignin without losing atom efficiency and lowering O/C ratio is a challenge in a bio-refinery concept. In this work, we report solid acid catalysed alkylation of lignin derived variety of monomers such as guaiacol, veretrole, phenol, anisole, and catechol using numerous alcohols as alkylating agents. Results elaborate that the type of acidity and structure of catalyst play important role in achieving higher dialkylated products (DAP). With 85% conversion of guaiacol, 30.9% DAP formation was achieved at 250 degrees C within 2 h. A unique substrate adsorption study on the catalyst surface and effect of solubility of substrates on the activity of catalyst is evaluated. Catalyst was observed to be recyclable with marginal loss in the activity due to handling error.
Keywords: Alcohols; Alkylation; lignin; Monomers; solid acid catalyst; Up-gradation

Alpha-, beta- and gamma-cellulose quantification and two-stage concentrated-dilute acid lignin recovery from three rice husks: lignin characterization and depolymerization - Singh, Sandip K.; Dhepe, Paresh L. (Waste and Biomass Valorization, 2022)
Investigations on the compositional analysis of lignocellulosic materials and their properties upon recovery are essential to be studied in order to examine the effects of recovery method, their dependency on the substrate, etc. In this work, three rice husks (RHs) samples were subjected for alpha-, beta- and gamma-cellulose, pentosan, and silica quantifications. Correlations between the source of biomass, lignin recovery by two-stage concentrated and dilute sulphuric acid treatment, their properties and their depolymerization into low molecular mass aromatic fractions using homogeneous and heterogeneous Bronsted acidic ionic liquids as catalysts, is carried out. Correlation between the properties of RHs and recovered lignin were performed using destructive (CHNS, TGA, ICP-OES, etc.) and non-destructive (XRD, UV-Visible, FT-IR, and C-13 CP-MAS NMR) analytical techniques. It was observed that the recovered lignin was polysaccharides free and associated with dibenzodioxocin, spirodienone, and tricin type moieties with variable intensities. The effects of lignin structures showed a change of depolymerisation product pattern. [GRAPHICS] .
Keywords: Holocellulose; Homogeneous and heterogeneous catalysts; lignin; Rice husks